SPEECH ACTS EQUIVALENCE OF AUDIOVISUAL TRANSLATION ON ENOLA HOLMES NETFLIX MOVIE SUBTITLE - Violita Violita; Hayatul Cholsy (Universitas Lambung Mangkurat, 2022)
this research discusses the speech act equivalence involving translation of English-Indonesian subtitle of Enola Holmes Netflix movie. Since pragmatic equivalence is consider as to be the suitable one to be analyzed in Audiovisual Translation (AVT), this research look closely in case of translating the subtitle especially the movie with genre of adventure and mystery. This audiovisual translation research employs qualitative descriptive with the research design of content analysis. The data is taken from the subtitle Netflix movie of Enola Holmes. According to the result of this research, it shows some circumstances firstly the ST that is translated equivalent in its speech act can present the message equivalent with the context of the story. Secondly, the translation that cannot reach the speech act equivalency is less able to bring the context of the story into the TT translation. In addition, the implication exists in utterances present in ST can be conveyed in the TT if the speech act equivalency is achieved. Otherwise, the implication that exists in utterances present in ST cannot be portrayed in TT if the speech act equivalency cannot be achieved.